2023
DOI: 10.3390/plants12091824
|View full text |Cite
|
Sign up to set email alerts
|

Garlic Ecotypes Utilise Different Morphological, Physiological and Biochemical Mechanisms to Cope with Drought Stress

Abstract: Drought negatively affects plants by altering morphological, physiological and metabolic processes and ultimately reducing yields. Garlic (Allium sativum L.), an important member of the Alliaceae family, is also sensitive to drought and maximizing the yield of garlic bulbs is largely dependent on water availability. The objective of this study was to determine the effects of drought stress on morphological and physiological characteristics, as well as on phenolic, sugar, inulin and free amino acid content and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
1
3
0
Order By: Relevance
“…In addition, we observed a significant correlation between TPC and TAA under high-temperature stress conditions. Similar findings were found in several studies [70,71], suggesting that the total antioxidant activity largely depends on the presence of large amounts of phenolic compounds [72]. Our results also revealed a positive correlation between APX and both CAT and TPC under drought stress.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we observed a significant correlation between TPC and TAA under high-temperature stress conditions. Similar findings were found in several studies [70,71], suggesting that the total antioxidant activity largely depends on the presence of large amounts of phenolic compounds [72]. Our results also revealed a positive correlation between APX and both CAT and TPC under drought stress.…”
Section: Discussionsupporting
confidence: 92%
“…In a study reported by Habuš Jerčić et al on two Croatian garlic landraces (Istarski bijeli i Istarski crveni), the authors reported a significant decrease in total phenolic content in the Istarski crveni ecotype, but also a significantly lower antioxidant activity as measured by FRAP caused by drought-induced stress. In the case of Istarski bijeli, the authors reported no significant change in total phenolic content, but a significant increase in antioxidant capacity (DPPH) [ 42 ]. The authors also reported a significant increase in proline content in both garlic landraces and a significant increase in amino acid content [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Istarski bijeli, the authors reported no significant change in total phenolic content, but a significant increase in antioxidant capacity (DPPH) [ 42 ]. The authors also reported a significant increase in proline content in both garlic landraces and a significant increase in amino acid content [ 42 ]. A study reported by Rodrigues et al also showed an increase in total phenolic content in red onions due to drought conditions [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plant phenotypic variation refers to the ability of a plant to change its phenotype in response to environmental factors, including the type of substrate in which it grows [ 1 , 2 , 3 , 4 ]. Variation in the phenotypic expression of traits of a given organism under the influence of environmental factors affects its development and ecology [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%